2012
DOI: 10.1007/s10549-012-2127-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mammographic density on breast tumor characteristics

Abstract: Mammographic density (MD) is a well-established risk factor for breast cancer. Whether MD influences the tumor phenotype remains to be clarified. Previous studies are highly inconsistent and most lack important covariate information. This is a case-only study within a population-based case-control study. Cases were all postmenopausal women, aged 50-74 years, with incident breast cancer, diagnosed 1993-1995, and with no history of previous cancer (n = 2,720). 1,747 women with mammograms and information on tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 46 publications
1
37
1
Order By: Relevance
“…Epidemiological studies have shown that mammographic density is not associated with any particular breast cancer sub-type [26,27], while some studies suggest that mammographic density is more strongly associated with ER-positive rather than ER-negative breast cancers [28,29]. Although the majority of human breast cancers are ERpositive and arise from epithelial tissues, we found no association between epithelial ER and proportions of epithelial and stromal tissue in any of the statistical models employed.…”
Section: Discussioncontrasting
confidence: 74%
“…Epidemiological studies have shown that mammographic density is not associated with any particular breast cancer sub-type [26,27], while some studies suggest that mammographic density is more strongly associated with ER-positive rather than ER-negative breast cancers [28,29]. Although the majority of human breast cancers are ERpositive and arise from epithelial tissues, we found no association between epithelial ER and proportions of epithelial and stromal tissue in any of the statistical models employed.…”
Section: Discussioncontrasting
confidence: 74%
“…For this study, the inclusion criteria were further refined to include only postmenopausal women who had no prior diagnosis of cancer other than nonmelanoma skin cancer (see Eriksson et al [14] for details). The study base thus consisted of 2,720 breast cancer cases.…”
Section: Methodsmentioning
confidence: 99%
“…This is theoretically plausible because MD has consistently been shown to be associated with the stromal composition of the breast [5-9], and the stroma plays an important part in tumor progression [10]. There is also some evidence that MD is associated with more aggressive tumor characteristics [11-13], but most studies have found no association between MD and tumor characteristics [14-19]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been established that tumors seen in BRCA1 carriers are more likely to be grade III and of the medullary subtype than sporadic cancers (25), but there are little data on association of other risk factors and histologic features. Reports on the associations of breast density with prognostic factors such as tumor grade, estrogen receptor (ER) status, and HER2 status have been inconclusive (26,27), although one recent study did show an association between breast density and high-grade tumors, ER-negative tumors, and in situ versus invasive tumors (27). Breast density has also been associated with an increased risk of local and locoregional recurrence (28) but not with distant metastasis or survival.…”
Section: Are There Features Of the Patient Population That Would Be Smentioning
confidence: 99%